FROM THE HISTORY OF ARCHAEOLOGICAL STUDY OF KABARDINO-BALKARIA: PROFESSOR KSPI KONSTANTIN EDUARDOVICH GRINEVICH - MURATOVA, E.G.; ORTANOVA, Yu.A. (Kavkazologiya, 2021)
The article is devoted to the issues of the origin and formation of the archaeological study of Kabardino-Balkaria as one of the areas of scientific research at the Kabardino-Balkarian State Pedagogical Institute (since 1957 – the Kabardino-Balkarian State University). The scientific and pedagogical activity of one of the first professors of the historical department, a well-known specialist in the field of ancient history, Konstantin Eduardovich Grinevich is shown. In 1949, he led the Kabardian archaeological expedition, the result of which was the compilation of an archaeological map of the republic. K.E. Grinevich made a great contribution to the study of the cultural heritage of Kabardino-Balkaria and the training of young personnel in the field of archeology.